Aluminum nitride sintered compact and electrostatic chuck

By incorporating rare earth oxide and magnesium oxide into aluminum nitride powder to form a composite oxide and magnesium oxide interface, the temperature dependence of volume resistivity is reduced, enabling effective J-R force type electrostatic chucking over a wide temperature range.

JP2025000176APending Publication Date: 2025-01-07NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023099882
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Conventional aluminum nitride sintered bodies exhibit a large temperature dependence of volume resistivity, limiting the temperature range for effective J-R force type electrostatic adsorption.

Method used

A novel aluminum nitride sintered body is developed by mixing aluminum nitride powder with rare earth oxide and magnesium oxide, forming a composite oxide and magnesium oxide at the particle interface, which reduces temperature dependence and maintains suitable volume resistivity across a wide temperature range.

Benefits of technology

The new aluminum nitride sintered body maintains a volume resistivity suitable for J-R force type electrostatic chucking from -50°C to 600°C, ensuring effective wafer holding in semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000176000001_ABST
    Figure 2025000176000001_ABST
Patent Text Reader

Abstract

To provide an aluminum nitride sintered compact and the like that maintain volume resistivity suitable for J-R force type electrostatic adsorption in a wide temperature range.SOLUTION: An aluminum nitride sintered compact 100 comprises aluminum nitride as a main component, a complex oxide including a rare earth element and aluminum, and magnesium oxide. In the aluminum nitride sintered compact 100, magnesium oxide exists in particles 2 of aluminum nitride, the complex oxide and magnesium oxide exist in a part 3 between the particles 2 of aluminum nitride, and an aluminum nitride particle interface phase containing aluminum, a nitrogen element, a rare earth element, magnesium and an oxygen element exists in a whole particle interface 4 of aluminum nitride. A ratio (Rmax / Rmin) between a maximum value Rmax and a minimum value Rmin of the volume resistivity of the aluminum nitride sintered compact in the range of -50°C to 600°C is 100 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum nitride sintered body and an electrostatic chuck. [Background technology]

[0002] A heater-equipped electrostatic chuck capable of holding a wafer is known as a semiconductor manufacturing device. A JR force type electrostatic chuck is known to adsorb a wafer by utilizing the Johnsen-Rahbek force (JR force) generated at the interface between the wafer and the electrostatic chuck.

[0003] In the JR force type electrostatic chuck, the material has a certain volume resistivity (10 9 ~10 12 It is desirable to use a ceramic material with a volume resistivity of about Ω·cm. For this reason, aluminum nitride sintered bodies, which contain aluminum nitride as the main component, have conventionally been used as ceramic materials with such a volume resistivity (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-52090 Summary of the Invention [Problem to be solved by the invention]

[0005] The volume resistivity of sintered aluminum nitride is highly temperature dependent. Therefore, the temperature range in which conventional sintered aluminum nitride can function as an electrostatic chuck of the JR force type is limited.

[0006] An object of the present invention is to provide an aluminum nitride sintered body that maintains a volume resistivity suitable for JR force type electrostatic chucking over a wide temperature range, and an electrostatic chuck using the aluminum nitride sintered body. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the inventors have found that when raw material powders are mixed so that the rare earth oxide powder and magnesium oxide powder are coated on the surface of the aluminum nitride powder, and the resulting mixture is used to produce an aluminum nitride sintered body, an aluminum nitride particle interface phase containing aluminum, nitrogen element, rare earth element, magnesium and oxygen element is formed throughout each particle interface of aluminum nitride contained in the aluminum nitride sintered body, and that this aluminum nitride particle interface phase has a lower volume resistivity and a smaller temperature dependency of volume resistivity than composite oxides containing rare earth elements and aluminum, and magnesium oxide, and therefore serves as a conductive path in the aluminum nitride sintered body, which led to the completion of the present invention.

[0008] The means for solving the above problems are as follows. <1> An aluminum nitride sintered body containing aluminum nitride as a main component, a composite oxide containing a rare earth element and aluminum, and magnesium oxide, wherein the magnesium oxide is present within the aluminum nitride particles, the composite oxide and the magnesium oxide are present in some of the spaces between the aluminum nitride particles, and an aluminum nitride particle interface phase containing aluminum, nitrogen element, rare earth element, magnesium and oxygen element is present throughout the aluminum nitride particle interface, and the aluminum nitride sintered body has a ratio (Rmax / Rmin) of the maximum volume resistivity Rmax to the minimum volume resistivity Rmin in the temperature range of -50°C to 600°C of 100 or less.

[0009] <2> When the mass of the aluminum nitride is taken as 100, the mass a of the composite oxide and the mass b of the magnesium oxide satisfy the following formulas (1) and (2): <1> The aluminum nitride sintered body according to claim 1. 3≦a≦10 (1) 3≦b≦10 (2)

[0010] <3> The mass a and the mass b satisfy the following formula (3): <2> The aluminum nitride sintered body according to claim 1. 0

[0011] <4> The aluminum nitride has an average particle size of 1.0 μm or more and 3.0 μm or less. <1> from <3> 13. The aluminum nitride sintered body according to claim 12.

[0012] <5> The above <1> from <4> 1. An electrostatic chuck comprising the aluminum nitride sintered body according to any one of the above. Effect of the Invention

[0013] According to the present invention, it is possible to provide an aluminum nitride sintered body which maintains a volume resistivity suitable for JR force type electrostatic chucking over a wide temperature range, and an electrostatic chuck using the aluminum nitride sintered body. [Brief description of the drawings]

[0014] [Figure 1] An explanatory diagram showing a schematic cross section of an aluminum nitride sintered body. [Diagram 2] FIG. 1 is an explanatory diagram showing an electrostatic chuck produced using the aluminum nitride sintered body of the present embodiment. [Diagram 3] FIG. 1 shows the results of element mapping using STEM images for the aluminum nitride sintered body of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] (Aluminum nitride sintered body) 1 is an explanatory diagram that typically shows a cut surface of an aluminum nitride sintered body 100. The aluminum nitride sintered body 100 of this embodiment contains aluminum nitride 2 as a main component, a composite oxide containing a rare earth element and aluminum (hereinafter, may be referred to as "R-Al composite oxide"), and magnesium oxide.

[0016] ​Magnesium oxide is present within the grains of aluminum nitride 2. In addition, as shown in Fig. 1, in the aluminum nitride sintered body 100, R-Al composite oxide and magnesium oxide are present in some of the spaces between the grains of aluminum nitride 2 (for example, grain boundary triple points of aluminum nitride) 3. In addition, an aluminum nitride grain interface phase containing aluminum, nitrogen element, rare earth element, magnesium and oxygen element is present throughout grain interface 4 of aluminum nitride 2.

[0017] In the aluminum nitride sintered body 100 of this embodiment, the ratio (Rmax / Rmin) of the maximum value Rmax to the minimum value Rmin of the volume resistivity in the range of -50°C to 600°C is 100 or less.

[0018] (Aluminum Nitride) Aluminum nitride (AlN) is the main component of the aluminum nitride sintered body. The content of aluminum nitride in the aluminum nitride sintered body (100 mass%) is 70 mass% or more, preferably 80 mass% or more, and more preferably 90 mass% or more. The aluminum nitride sintered body is known to have excellent mechanical strength and thermal shock resistance, high volume resistivity and thermal conductivity, and high corrosion resistance, especially against halogen gases and halogen plasmas.

[0019] As described above, magnesium oxide is present within the aluminum nitride grains (crystal grains).

[0020] In the aluminum nitride sintered body, the aluminum nitride preferably forms crystal grains having an average grain size of 1.0 μm or more and 3.0 μm or less. The average grain size is more preferably 1.0 μm or more and 2.5 μm or less. When the average grain size is in this range, the aluminum nitride sintered body contains many grain boundaries of aluminum nitride crystal grains, and it is easy to make R-Al composite oxide and magnesium oxide exist between them (for example, grain boundary triple points). The method for measuring the average grain size will be described later.

[0021] (R-Al composite oxide) The aluminum nitride sintered body of the present embodiment contains a composite oxide (R-Al composite oxide) containing a rare earth element (R) and aluminum (Al). As described above, the R-Al composite oxide is present in some of the spaces between the particles of the aluminum nitride 2 (for example, the grain boundary triple points of the aluminum nitride) 3.

[0022] It is known that aluminum nitride raw material powder is oxidized in the air, and oxygen substitutes and dissolves at the nitrogen atom position, which creates defects (vacancies) in the aluminum nitride and reduces its insulating properties. In the aluminum nitride manufacturing process, rare earth oxide powder containing rare earth elements is added to aluminum nitride powder and sintered, and the aluminum oxide contained in the aluminum nitride reacts with the rare earth oxide to produce an R-Al composite oxide containing rare earth elements and aluminum. This removes the dissolved oxygen in the aluminum nitride, making it possible to suppress a decrease in volume resistivity.

[0023] Examples of rare earth elements (R) contained in the R-Al composite oxide include yttrium (Y), lanthanum (La), cerium (Ce), holmium (Ho), gadolinium (Gd), neodymium (Nd), samarium (Sm), dysprosium (Dy), ytterbium (Yb), erbium (Er), and lutetium (Lu). As long as the object of the present invention is not impaired, these elements may be used alone or in combination of two or more. Among these, yttrium is particularly preferred.

[0024] In R-Al composite oxides, rare earth elements and aluminum are combined in a specific ratio to form a garnet-type (R 3 Al 5 O 12 ), Perovskite type (RAlO 3 ), Monoclinic type (R 4 Al 2 O 9 Among them, R-Al composite oxides having a garnet-type crystal structure with high volume resistivity are preferred. When yttrium is used as the rare earth element, the R-Al composite oxide is preferably Y 3 Al 5 O12 (YAG), YAlO 3 (YAP), Y 4 Al 2 O 9 Crystal structures such as (YAM) are formed.

[0025] In the aluminum nitride sintered body of this embodiment, when the mass of aluminum nitride is taken as 100 (100 parts by mass), the mass (parts by mass) a of the R-Al composite oxide preferably satisfies the following formula (1).

[0026] 3≦a≦10 (1)

[0027] When the mass a of the R-Al composite oxide is within the above range, the effect of the aluminum nitride particle interface phase can be obtained, and the temperature dependency of the volume resistivity can be suppressed.

[0028] (Magnesium oxide) The aluminum nitride sintered body of this embodiment contains magnesium oxide (MgO), which is present in some of the spaces between the grains of the aluminum nitride 2 (for example, grain boundary triple points 3 of the aluminum nitride) as described above.

[0029] By allowing magnesium oxide, which has a high volume resistivity, to exist between aluminum nitride particles, a high volume resistivity can be achieved. As a measure to increase the specific resistance of aluminum nitride particles, it is possible to add magnesium oxide powder to aluminum nitride powder and sinter it to produce an aluminum nitride sintered body. In this case, magnesium oxide dissolves in the aluminum nitride particles to form a barrier, and magnesium dissolves in defects (holes) in the aluminum nitride to replenish the defects in the aluminum nitride. As a result, magnesium oxide and magnesium are contained in the aluminum nitride particles in the aluminum nitride sintered body.

[0030] In the aluminum nitride sintered body of this embodiment, when the mass of aluminum nitride is taken as 100 (100 parts by mass), the mass (parts by mass) b of magnesium oxide preferably satisfies the following formula (2).

[0031] 3≦b≦10 (2)

[0032] When the mass b of magnesium oxide is within the above range, magnesium oxide can be dissolved in aluminum nitride particles while being present between the aluminum nitride particles, and defects during sintering (sintering inhibition) due to the presence of excess magnesium oxide can be suppressed.

[0033] In addition, in the aluminum nitride sintered body of this embodiment, when the mass of aluminum nitride is 100 (100 parts by mass), it is preferable that the mass (parts by mass) a of the R-Al composite oxide and the mass (parts by mass) b of the magnesium oxide satisfy the following formula (3).

[0034] 0

[0035] When the ratio of the mass a of the R-Al composite oxide to the mass b of the magnesium oxide (the proportion of mass b to mass a) is within the above range, the aluminum nitride sintered body can easily exhibit a predetermined volume resistivity over a wide temperature range (from -50°C to 600°C) while maintaining a good balance of the R-Al composite oxide and magnesium oxide between the aluminum nitride particles.

[0036] (Aluminum nitride particle interface phase) In the aluminum nitride sintered body of this embodiment, as described above, an aluminum nitride grain interface phase containing aluminum, nitrogen element, rare earth element, magnesium and oxygen element is present throughout the grain interfaces of the aluminum nitride.

[0037] ​The aluminum nitride grain interface phase exists over the entire grain interface of each aluminum nitride contained in the aluminum nitride sintered body. Such an aluminum nitride grain interface phase has a lower volume resistivity and a smaller temperature dependency of the volume resistivity than the R-Al composite oxide and magnesium oxide existing in the aluminum nitride grains in which magnesium oxide is dissolved, and between the aluminum nitride grains. Therefore, in the aluminum nitride sintered body of this embodiment, the aluminum nitride grain interface phase existing over the entire grain interface of each aluminum nitride becomes a conductive path. The volume resistivity of this aluminum nitride grain interface phase is the volume resistivity of the aluminum nitride sintered body of this embodiment.

[0038] (Method of manufacturing sintered aluminum nitride body) The aluminum nitride sintered body according to this embodiment is manufactured through, for example, a mixing step, a press molding step, and a sintering step.

[0039] (Mixing process) The mixing step is a step of mixing the raw material powders of aluminum nitride powder, rare earth element powder, and magnesium oxide powder in the following manner to obtain a mixture thereof.

[0040] In the mixing step, the raw material powders are mixed together using a known method such as a particle composite device, a powder sputtering device, etc., so that the surface of the aluminum nitride powder can be coated with the rare earth oxide powder (e.g., yttrium oxide powder) and the magnesium oxide powder. The mixing step may be performed in a wet or dry manner as long as it does not impair the object of the present invention.

[0041] (Press molding process) The press molding process is a process in which the mixture obtained after the mixing process is press molded into a predetermined shape. The press molding process is performed by a known molding method such as a die molding method, a cold isostatic pressing (CIP) method, a slip casting method, an extrusion molding method, etc. It is also possible to perform a combination of these methods. For example, after performing uniaxial press molding using a die press, an isostatic treatment is performed to obtain a molded body. This allows a more homogeneous and dense molded body to be obtained.

[0042] (Firing process) The firing step is a step of firing the molded body in order to sinter the molded body after the press molding step. The firing step is preferably carried out, for example, in an inert gas atmosphere under temperature conditions of 1000°C or higher and 2000°C or lower. The firing step may be carried out at normal pressure, but is preferably carried out under pressure by a hot press method. This makes it possible to obtain a more homogeneous and dense sintered body.

[0043] (Volume resistivity) The aluminum nitride sintered body of this embodiment has a ratio (Rmax / Rmin) of the maximum volume resistivity Rmax to the minimum volume resistivity Rmin in the temperature range of −50° C. to 600° C. of not more than 100. The method for measuring the volume resistivity will be described later.

[0044] The aluminum nitride sintered body of this embodiment has a melting point of 1.0×10 at −50° C. 10 Ω cm or more 1.0×10 12 It exhibits a volume resistivity of less than Ω·cm.

[0045] In addition, the aluminum nitride sintered body of the present embodiment has a melting point of 1.0×10 10 Ω cm or more 1.0×10 11 It exhibits a volume resistivity of less than Ω·cm.

[0046] In addition, the aluminum nitride sintered body of this embodiment has a melting point of 1.0×10 9 Ω cm or more 1.0×10 10 It exhibits a volume resistivity of less than Ω·cm.

[0047] The aluminum nitride sintered body of this embodiment maintains a volume resistivity suitable for JR force type electrostatic adsorption over a wide temperature range (from −50° C. to 600° C.).

[0048] (Electrostatic Chuck) The aluminum nitride sintered body of this embodiment is suitable for use in a JR force type electrostatic chuck. Fig. 2 is an explanatory diagram showing an electrostatic chuck 1 manufactured using the aluminum nitride sintered body of this embodiment. The electrostatic chuck 1 holds a wafer W, which is an object to be processed, in, for example, a semiconductor manufacturing device.

[0049] 2, the electrostatic chuck 1 includes a ceramic plate 10 made of the aluminum nitride sintered body of this embodiment, and an electrode (electrostatic electrode) 20 made of a conductor such as metal embedded inside the ceramic plate 10. When a voltage is applied to the electrode 20, an electric charge of the opposite polarity is generated on the back surface of the wafer W arranged opposite to the front surface of the ceramic plate 10. A minute current flows in the interface gap between the ceramic plate 10, which is a dielectric, and the wafer W, which is the processing object, and as a result of the electric charge polarization, the wafer W is strongly attracted to and held on the surface of the ceramic plate 10. The force that attracts the wafer W onto the ceramic plate 10 in this manner is the JR force. In order to generate the JR force, a force of 1.0×10 9 Ω cm or more 1.0×10 12 It is preferable to use a ceramic plate 10 having a volume resistivity of Ω·m or less.

[0050] As described above, the aluminum nitride sintered body of the present embodiment maintains a volume resistivity suitable for JR force type electrostatic attraction over a wide temperature range (−50° C. to 600° C.), and is therefore extremely suitable as a material for forming the above-described electrostatic chuck 1. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0052] [Examples 1 to 9, Comparative Examples 1 to 4] (Preparation of sintered aluminum nitride) The aluminum nitride powder, the yttrium oxide powder, and the magnesium oxide powder were each weighed so that the R-Al composite oxide and the magnesium oxide in the aluminum nitride sintered body were in the amounts shown in Table 1. In order to coat the surface of the aluminum nitride powder with the yttrium oxide powder and the magnesium oxide powder, the weighed raw material powders (aluminum nitride powder, yttrium oxide powder, and magnesium oxide powder) were mixed using a particle composite device. The mixed powder obtained was uniaxially pressed by a die press under a press pressure of 12 MPa. The obtained molded product was further subjected to a hydrostatic pressure treatment at 147 MPa to obtain a disk-shaped molded product with a diameter of 60 mm and a thickness of about 9 mm. Then, this molded product was packed in a carbon die and sintered by a hot press method in a nitrogen atmosphere under conditions of a sintering temperature of 1830°C, a holding time of 2 hours, and a pressure of 4.4 MPa. The aluminum nitride sintered products of Examples 1 to 9 and Comparative Examples 1 to 4 were manufactured by the above-mentioned method.

[0053] Comparative Example 5 An aluminum nitride sintered body of Comparative Example 5 was produced in the same manner as in Example 1, except that the weighed raw material powders were mixed in a ball mill as described below without using a particle composite device to obtain a mixed powder. In Comparative Example 5, the weighed raw material powders were added to ethanol as a solvent, mixed in a ball mill, and the mixture obtained was dried to obtain a mixed powder.

[0054] [Analysis and Evaluation] For the aluminum nitride sintered bodies according to each of the Examples and Comparative Examples, the mass ratio, average particle size, and volume resistivity were measured by the methods described below.

[0055] (mass ratio) The powder obtained by pulverizing the aluminum nitride sintered body was subjected to measurement of the diffraction pattern using a synchrotron X-ray diffractometer. The obtained diffraction pattern was quantitatively analyzed using the WPPF (Whole Powder Pattern Fitting) method to calculate the mass ratio (b / a) of the R-Al composite oxide to magnesium oxide. The results are shown in Table 1. In Table 1, the amount a (parts by mass) of the R-Al composite oxide and the amount b (parts by mass) of magnesium oxide are amounts relative to 100 parts by mass of aluminum nitride.

[0056] (Average particle size) The cut surface of the aluminum nitride sintered body was observed by a SEM (Scanning Electron Microscope), and the average particle size of the aluminum nitride particles contained in the aluminum nitride sintered body was measured from the observed image by the intercept method. The results are shown in Table 1.

[0057] (Volume resistivity) Test pieces were cut out from the aluminum nitride sintered body in accordance with JIS C2141, and the volume resistivity (Ω cm) of the test pieces was measured in a nitrogen atmosphere at temperatures of -50°C, 300°C, and 600°C by the DC three-terminal method in accordance with JIS C2141. The results are shown in Table 1.

[0058] [Table 1]

[0059] As shown in Table 1, the aluminum nitride sintered bodies of Examples 1 to 9 all had a ratio (Rmax / Rmin) of the maximum volume resistivity Rmax to the minimum volume resistivity Rmin in the temperature range of -50°C to 600°C of 100 or less. Therefore, it was confirmed that the aluminum nitride sintered bodies of Examples 1 to 9 maintained a volume resistivity suitable for JR force type electrostatic adsorption in a wide temperature range of -50°C to 600°C.

[0060] In each of these Examples, an aluminum nitride grain interface phase containing aluminum, nitrogen element, rare earth element, magnesium and oxygen element is formed over the entire grain interface of aluminum nitride contained in the aluminum nitride sintered body.

[0061] It is presumed that the aluminum nitride grain interface phase reduces the band gap of the aluminum nitride grain interface, thereby decreasing the volume resistivity of the aluminum nitride grain interface, and that the entire grain interface of aluminum nitride where such an aluminum nitride grain interface phase exists serves as a conductive path in the aluminum nitride sintered body.

[0062] It is also presumed that the presence of such an aluminum nitride grain interface phase over the entire grain interface of aluminum nitride reduces the temperature dependence of the volume resistivity in the aluminum nitride sintered body.

[0063] The aluminum nitride sintered body of Comparative Example 1 does not contain magnesium oxide. The aluminum nitride sintered body of Comparative Example 2 has an excessively low magnesium oxide content. In the aluminum nitride sintered bodies of Comparative Examples 1 and 2, the ratio (Rmax / Rmin) of the maximum value Rmax to the minimum value Rmin significantly exceeded 100. In the aluminum nitride sintered bodies of Comparative Examples 1 and 2, the volume resistivity was too high under low temperature conditions (-50°C) and was too low under high temperature conditions (600°C).

[0064] The aluminum nitride sintered body of Comparative Example 3 is a case where the ratio (b / a) of mass a to mass b (proportion of mass b to mass a) is too large. In this case as well, the ratio (Rmax / Rmin) of maximum value Rmax to minimum value Rmin significantly exceeds 100. In the case of Comparative Example 3, the volume resistivity is too high at low temperature (-50°C), and even at 300°C, the volume resistivity is too high.

[0065] The aluminum nitride sintered body of Comparative Example 4 has an excessively large value of mass a. In this case, the ratio (Rmax / Rmin) of the maximum value Rmax to the minimum value Rmin significantly exceeded 100. In the case of Comparative Example 4, the volume resistivity at low temperature (-50°C) was too high, and the volume resistivity at high temperature (600°C) was too low.

[0066] The aluminum nitride sintered body of Comparative Example 5 differs from Example 2 in that, although the raw material powders (mass, ratio) used were the same as those of Example 2, no particle composite device was used when mixing them. In the case of Comparative Example 5, the ratio (Rmax / Rmin) of the maximum value Rmax to the minimum value Rmin significantly exceeded 100. In the case of Comparative Example 5, the volume resistivity was too high at low temperature (-50°C), and also at 300°C.

[0067] In Comparative Example 5, it is presumed that the amounts of yttrium oxide powder and magnesium oxide powder adhered to the surface of the aluminum nitride powder when the raw material powders were mixed were insufficient, and therefore an aluminum nitride particle interface phase that could serve as a conductive path, as in each of the examples, was not formed.

[0068] (Elemental mapping) For each of the aluminum nitride sintered bodies of Examples 1 to 9, element mapping was performed using STEM images of the cut surface of each aluminum nitride sintered body using STEM (Scanning Transmission Electron Microscope)-EDS (Energy Dispersive X-ray Spectroscopy). As a result, in the case of Examples 1 to 9, it was confirmed that rare earth elements, magnesium, and oxygen elements were present throughout the aluminum nitride particle interface. In addition, it was confirmed that aluminum and nitrogen elements were present not only in the aluminum nitride particle interface but also throughout the aluminum nitride particle (i.e., the entire aluminum nitride sintered body), such as within the aluminum nitride particle. In the case of Examples 1 to 9, it can be said that the aluminum, nitrogen, rare earth, magnesium, and oxygen elements present throughout the grain interface of each aluminum nitride contained in the aluminum nitride sintered body form an aluminum nitride particle interface phase.

[0069] Here, as a representative example, the element mapping results of Example 1 are shown in Fig. 3. Fig. 3 is a diagram (photograph) showing the result of element mapping of the aluminum nitride sintered body of Example 1 using a STEM image.

[0070] As shown in FIG. 3, it was confirmed that in the aluminum nitride sintered body of Example 1, rare earth elements, magnesium, and oxygen elements were present throughout the aluminum nitride particle interfaces, as well as aluminum and nitrogen elements. [Explanation of symbols]

[0071] 100...aluminum nitride sintered body, 1...electrostatic chuck, 10...ceramic plate, 20...electrode, 2...aluminum nitride particle, 3...between aluminum nitride particles, 4...particle interface of aluminum nitride

Claims

1. The main component is aluminum nitride, A composite oxide containing a rare earth element and aluminum; An aluminum nitride sintered body containing magnesium oxide, The magnesium oxide is present within the aluminum nitride particles, the composite oxide and the magnesium oxide are present in some of the spaces between the aluminum nitride particles, an aluminum nitride grain interface phase containing aluminum, a nitrogen element, a rare earth element, magnesium and an oxygen element is present throughout the grain interface of the aluminum nitride, An aluminum nitride sintered body having a ratio (Rmax / Rmin) of the maximum volume resistivity Rmax to the minimum volume resistivity Rmin in the temperature range of -50°C to 600°C of 100 or less.

2. 2. The aluminum nitride sintered body according to claim 1, wherein, when the mass of the aluminum nitride is taken as 100, the mass a of the composite oxide and the mass b of the magnesium oxide satisfy the following formulas (1) and (2). 3≦a≦10 (1) 3≦b≦10 (2)

3. The aluminum nitride sintered body according to claim 2 , wherein the mass a and the mass b satisfy the following formula (3): 0<b / a≦3...(3)

4. 4. The aluminum nitride sintered body according to claim 1, wherein the aluminum nitride has an average particle size of 1.0 μm or more and 3.0 μm or less.

5. An electrostatic chuck comprising the aluminum nitride sintered body according to claim 1 .

Citation Information

Patent Citations

  • Aluminum nitride sintered body, and electrostatic chuck

    JP2022052090A